Genetic aspects of lactase deficiency in indigenous populations of Siberia - B. A. Malyarchuk (Вавиловский журнал генетики и селекции)
The ability to metabolize lactose in adulthood is associated with the persistence of lactase enzyme activity. In European populations, lactase persistence is determined mainly by the presence of the rs4988235-T variant in the MCM6 gene, which increases the expression of the LCT gene, encoding lactase. The highest rates of lactase persistence are characteristic of Europeans, and the lowest rates are found in East Asian populations. Analysis of published data on the distribution of the hypolactasia-associated variant rs4988235-C in the populations of Central Asia and Siberia showed that the frequency of this variant increases in the northeastern direction. The frequency of this allele is 87 % in Central Asia, 90.6 % in Southern Siberia, and 92.9 % in Northeastern Siberia. Consequently, the ability of the population to metabolize lactose decreases in the same geographical direction. The analysis of paleogenomic data has shown that the higher frequency of the rs4988235-T allele in populations of Central Asia and Southern Siberia is associated with the eastward spread of ancient populations of the Eastern European steppes, starting from the Bronze Age. The results of polymorphism analysis of exons and adjacent introns of the MCM6 and LCT genes in indigenous populations of Siberia indicate the possibility that polymorphic variants may potentially be related to lactose metabolism exist in East Asian populations. In East Asian populations, including Siberian ethnic groups, a ~26.5 thousand nucleotide pairs long region of the MCM6 gene, including a combination of the rs4988285-A, rs2070069-G, rs3087353-T, and rs2070068-A alleles, was found. The rs4988285 and rs2070069 loci are located in the enhancer region that regulates the activity of the LCT gene. Analysis of paleogenomic sequences showed that the genomes of Denisovans and Neanderthals are characterized by the above combination of alleles of the MCM6 gene. Thus, the haplotype discovered appears to be archaic. It could have been inherited from a common ancestor of modern humans, Neanderthals, and Denisovans, or it could have been acquired by hybridization with Denisovans or Neanderthals. The data obtained indicate a possible functional significance of archaic variants of the MCM6 gene.